NARRATIVE REVIEW : POLA BAKTERI, SENSITIVITAS DAN PENGGUNAAN ANTIBIOTIK PADA INFEKSI SALURAN KEMIH - Dita Ayulia Dwi Sandi; Okta Muthia Sari; Muhammad Ridho Maulana (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
Urinary Tract Infection (UTI) is an infectious disease that ranks second after respiratory tract infections, with a total of 8.1 million cases per year. The cause of UTI lies in the presence of microorganisms in the urinary tract, including the bladder, prostate, kidneys, and collecting ducts. Bacterial microorganisms are the primary cause of UTI. Generally, Urinary Tract Infection (UTI) is caused by common human flora and symbiotic life around the vaginal introitus, penile prepuce, perineum, and the surrounding anus. This study aims to identify bacterial types, treatment methods, and antibiotic sensitivity in urinary tract infections. The chosen method for this research is a narrative review of scientific studies related to urinary tract infections. Data sources were obtained from Google Scholar, ScienceDirect, and PubMed. The research articles used include 5 journals related to UTI bacterial patterns, 7 journals related to UTI therapy patterns, and 4 journals related to antibiotic sensitivity in UTI patients. Based on the analysis of bacterial patterns, Escherichia coli bacteria are the most common cause of UTI. Antibiotic therapy patterns can be used in the treatment of Urinary Tract Infection. The analysis of antibiotic sensitivity indicates that ciprofloxacin and gentamicin have the highest sensitivity to UTI.